Caligus turkiyensis n. sp. (Copepoda: caligidae) on the flathead grey mullet, Mugil cephalus (Linnaeus) (Mugiliformes: mugilidae) from the sea of Marmara, Turkey - Oktener, Ahmet (2024)
Caligus turkiyensis n. sp. is described from the body surface and fins of the flathead grey mullet, Mugil cephalus Linnaeus, 1758, collected in the Sea of Marmara in Turkey. The new species is easily distinguished from its congeners by the ratio of genital complex length/abdomen length, number of segments in abdomen, length of tines in the sternal furca, number of teeth on the mandible, position of the posterolateral corners of the genital complex relative to the abdomen, status of the recurved terminal claw of the antenna and postantennal process, ratio of length and anterior margin of the maxillule endopodite, process on myxal surface of maxilliped, ratio of first/third spine on fourth leg and existence of denticles on first spine of fourth leg in the female; total body length, process on myxal surface of maxilliped, number of plates and spine at terminal segment of antenna in the male. This study also includes records of Caligus apodus (Brian, 1924) and Caligus pageti Russel, 1925 on two mugilid species from the Sea of Marmara, Turkey. The Sea of Marmara is considered as a new locality for C. pageti.